Different nutritional-state indicators of HIV-positive individuals undergoing antiretroviral therapy - Geraix, J. [UNESP]; Carvalhaes, M. A.B.L. [UNESP]; Pereira, Paulo Câmara Marques [UNESP] (FapUNIFESP (SciELO), 2008)
This study aimed at learning about the nutritional profile of HIV-positive individuals undergoing antiretroviral therapy and at comparing the performance of nutritional-state indicators. A transversal study was performed on 94 patients attending the Tropical Diseases Outpatient Hospital of Botucatu Medical School (FMB) - UNESP. The body mass index (BMI) and the classification by Papini-Berto (PB) were used to evaluate nutritional state, aiming at detecting malnutrition and obesity. The waist-to-hips ratio (W/HR) and waist circumference (WC) were adopted for identification of abdominal obesity and lipodystrophy. According to BMI, most of the individuals were eutrophic, followed by 30.9% overweight and 6.4% malnourished. By using the PB classification, the frequency of malnourished increased (22.3%). The analysis of the PB classification in relation to BMI indicated that the former presented high sensitivity and good specificity for malnutrition diagnosis, namely 100% and 83%, respectively. The prevalence of abdominal obesity was 7.44% according to WC, and a higher prevalence (38.3%) was observed when taking W/HR into account. There was significant positive association between nutritional diagnosis according to PB and T CD4+ lymphocyte. The results support the use of PB classification for malnutrition detection as well as that of BMI and W/HR for overweight and fat redistribution.
Keywords: Antiretroviral therapy; HIV/AIDS; Nutritional indicators